1984
DOI: 10.2307/1590127
|View full text |Cite
|
Sign up to set email alerts
|

Field Trials to Test the Efficacy of Polyvalent Marek's Disease Vaccines in Broilers

Abstract: The efficacies of trivalent (Md11/75C + SB-1 + HVT), bivalent (SB-1 + HVT), and turkey herpesvirus (HVT) vaccines against Marek's disease (MD) were compared in commercial broiler flocks in four trials involving 11 farm locations and 486,300 chickens. In all four trials, chickens receiving polyvalent vaccines had lower leukosis (MD) condemnation rates than chickens vaccinated with HVT alone; when data were summarized for each vaccine type in each trial, condemnation rates for the bivalent- or trivalent-vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Unlike virulent MDV, which can effectively spread horizontally between weeks 3 and 5 after infection, resulting in infection of other chickens or reinfection (4,14), the horizontal transmission of avirulent strains is very poor or absent (24). Serotype 2 MDV and CVI988 spread horizontally 2 weeks after immunization (30,31), but neither attenuated MDV nor HVT does so (4,14), even though viral antigens can be detected for a limited period in the feather follicle epithelium of chickens infected with HVT (15,18,31,40). The CVI988 strain initially spread well by contact, but partial flock vaccination does not work in practice, as the spread of the vaccine strain was very poor and not rapid enough to precede infection with virulent strains from the field (1,29).…”
Section: Fig 5 Dynamics Of Neutralizing Antibodies In Spf White Legmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike virulent MDV, which can effectively spread horizontally between weeks 3 and 5 after infection, resulting in infection of other chickens or reinfection (4,14), the horizontal transmission of avirulent strains is very poor or absent (24). Serotype 2 MDV and CVI988 spread horizontally 2 weeks after immunization (30,31), but neither attenuated MDV nor HVT does so (4,14), even though viral antigens can be detected for a limited period in the feather follicle epithelium of chickens infected with HVT (15,18,31,40). The CVI988 strain initially spread well by contact, but partial flock vaccination does not work in practice, as the spread of the vaccine strain was very poor and not rapid enough to precede infection with virulent strains from the field (1,29).…”
Section: Fig 5 Dynamics Of Neutralizing Antibodies In Spf White Legmentioning
confidence: 99%
“…The CVI988 strain initially spread well by contact, but partial flock vaccination does not work in practice, as the spread of the vaccine strain was very poor and not rapid enough to precede infection with virulent strains from the field (1,29). By 2 weeks after vaccination, specific immunity to MD has been developed (31,33), which inhibits reinfection caused by limited cell-free vaccine viruses inhaled from dust or dander (8,26,40), resulting in the failure of the reinfection. This study demonstrated only one phase of productive infection in the chickens receiving a single vaccination and two phases of productive infection in revaccinated chickens within 7 weeks after immunization, suggesting that the productive infection caused by vaccine viruses shed from vaccinated chickens is not successful or that reactivation of latent viruses in PBLs does not occur; thus, there is no persistent antigen supply after vaccine viruses enter latency.…”
Section: Fig 5 Dynamics Of Neutralizing Antibodies In Spf White Legmentioning
confidence: 99%
See 1 more Smart Citation
“…It was probably due to imperfect vaccination practices and, in some countries, wrong hygienic conditions that led to reservoirs of viruses in poultry houses (Bourne, 1996). In response to the increasing number of MD outbreaks in vaccinated flocks, in the 1980s, new vaccines based on the non-oncogenic serotype-2 MDV were introduced in bivalent www.intechopen.com combination with HVT Witter et al, 1984). The use of polyvalent vaccine provided a better protection against MDV challenge (Witter, 1992).…”
Section: Vaccinationmentioning
confidence: 99%
“…Because vvMDV has emerged, improvement of the vaccines is urgently needed. Protection against vvMDV by inoculation of the combination of HVT and MDV2 strain SB1 has been demonstrated in laboratory experiments (Witter, 1982) and in field trials (Calnek et al, 1983;Witter et al, 1984). Further, Witter et al (1987) examined several vaccine candidates against vvMDV and demonstrated that some of the MDV2 isolates may be good vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%